2008
DOI: 10.1002/path.2422
|View full text |Cite
|
Sign up to set email alerts
|

Induction of centrosome amplification and chromosome instability in p53‐deficient lung cancer cells exposed to benzo[a]pyrene diol epoxide (B[a]PDE)

Abstract: Benzo[a]pyrene diol epoxide (B[a]PDE), the ultimate carcinogenic metabolite of benzo[a] pyrene, has been implicated in the mutagenesis of the p53 gene involved in smoking-associated lung cancer. To further understand the role of B[a]PDE in lung tumour progression, we investigated its effect on the numerical integrity of centrosomes and chromosome stability in lung cancer cells lacking p53. Exposure of p53-deficient H1299 lung cancer cells to B[a]PDE resulted in S-phase arrest, leading to abnormal centrosome am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…Benzo[a]pyrene diol epoxide (B[a]PDE), the ultimate carcinogenic metabolite of benzo [a]pyrene, has been implicated in the mutagenesis of the p53 gene, which is involved in smoking-associated lung cancer. Shinmura et al (2008) showed that the exposure of p53-deficient H1299 lung cancer cells to B[a]PDE resulted in S-phase arrest, leading to abnormal centrosome amplification. They also revealed that the centrosome amplification could be primarily attributed to excessive centrosome duplication, rather than to centriole splitting, and the forced expression of POLK DNA polymerase, which has the ability to bypass B[a]PDE-guanine lesions in an error-free manner, suppressing B[a]PDE-induced centrosome amplification.…”
Section: Centrosome Abnormalities In Human Lung Cancer: Mechanisms Camentioning
confidence: 99%
See 1 more Smart Citation
“…Benzo[a]pyrene diol epoxide (B[a]PDE), the ultimate carcinogenic metabolite of benzo [a]pyrene, has been implicated in the mutagenesis of the p53 gene, which is involved in smoking-associated lung cancer. Shinmura et al (2008) showed that the exposure of p53-deficient H1299 lung cancer cells to B[a]PDE resulted in S-phase arrest, leading to abnormal centrosome amplification. They also revealed that the centrosome amplification could be primarily attributed to excessive centrosome duplication, rather than to centriole splitting, and the forced expression of POLK DNA polymerase, which has the ability to bypass B[a]PDE-guanine lesions in an error-free manner, suppressing B[a]PDE-induced centrosome amplification.…”
Section: Centrosome Abnormalities In Human Lung Cancer: Mechanisms Camentioning
confidence: 99%
“…Numerical and functional abnormalities of centrosomes result in an increase in aberrant mitotic spindle formation, merotelic kinetochore-microtubule attachment errors, lagging chromosome formation, and chromosome segregation errors, all of which are thought to be possible causes of chromosome instability (Ganem et al, 2009;Nigg & Raff, 2009). Centrosome abnormalities and chromosome instability are characteristics of human lung cancer (Masuda and Takahashi, 2002;Koutsami et al, 2006;Jung et al, 2007;Shinmura et al, 2008), and abnormalities in genes responsible for centrosome regulation have been reported in lung cancer (Fukasawa, 2007;Lee et al, 2010). In this Review, the status of centrosome abnormalities in lung cancer, the mechanisms responsible for inducing centrosome abnormalities, and the relationship between centrosome abnormalities and chromosome instability are summarized.…”
Section: Introductionmentioning
confidence: 99%
“…10 Luciferase reporter assay p53-null human H1299 cells were transiently cotransfected with the p53 expression vector, firefly luciferase reporter vector pGL4.10 (Promega, Madison, WI) containing a fragment of the p21 (CDKN1A), BAX or MDM2 promoter and a Renilla luciferase reporter vector pGL4.74 (Promega), and 24 hr after transfection, luciferase activity was measured by a Dual-Luciferase Reporter Assay System (Promega) as described previously. 7 Colony formation assay p53-null H1299 cell lines were transfected with the p53 expression vector using Lipofectamine 2000 reagent (Invitrogen, Carlsbad, CA), followed by selection in media containing G418 antibiotics at 1 mg/ml for 2 weeks.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…CIN frequently occurs in human malignant tumors (Lengauer et al, 1998) and it is a major cause of genomic instability in colorectal cancer (Grady, 2004). Two causes of CIN have been reported: a defect in the spindle assembly checkpoint (SAC) and a defect in centrosome replication, both of which can be induced by a mutation in a checkpoint gene or by an exogenous agent (Pihan and Doxsey, 1999;Shinmura et al, 2008). As chromosomes are exposed to the greatest risk of CIN during mitosis, analysis of mitotic progression has become a focus of attention in the field of cancer research (Bharadwaj and Yu, 2004).…”
Section: Introductionmentioning
confidence: 99%